PENGARUH VARIABEL DEMOGRAFI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TENAGA MEDIS DAN PARAMEDIS STUDI PADA RUMAH SAKIT IBU DAN ANAK (RSIA) MUTIARA BUNDA - Rimayanti; Hastin Umi Anisah (Universitas Lambung Mangkurat, 2014)
Organizational Citizenship Behavior (OCB) is an attitude that is essential for the medical personnel so that the quality of care for patients is always awake, and loyalty to the organization can be improved. This study aims to investigate the influence of demographic variables and job satisfaction either partially or simultaneously on Organizational Citizenship Behavior (OCB) in medical and paramedical personnel in RSIA Mother of Pearl, which was tested using multiple regression analysis. The results of the study at 43 medical personnel revealed that demographic variables partially positive and significant effect on OCB, whereas job satisfaction is partially positive and significant effect on OCB. Demographic variables and job satisfaction have positive and significant effect on OCB. Based on these results, implications for the management of the hospital is that the demographics and job satisfaction should be considered in order to encourage OCB behaviors among medical and paramedical personnel, so that the satisfaction and comfort of the patient as well as the smooth operation of the hospital can be improved.